The Concept, Development, and Application of a Home-Based High-Definition tDCS for Bilateral Motor Cortex Modulation in Migraine and Pain - DaSilva, Alexandre F.; Datta, Abhishek; Swami, Jaiti; Kim, Dajung J.; Patil, Parag G.; Bikson, Marom (Frontiers in Pain Research, 2022)
Whereas, many debilitating chronic pain disorders are dominantly bilateral (e.g., fibromyalgia, chronic migraine), non-invasive and invasive cortical neuromodulation therapies predominantly apply unilateral stimulation. The development of excitatory stimulation targeting bilateral primary motor (M1) cortices could potentially expand its therapeutic effect to more global pain relief. However, this is hampered by increased procedural and technical complexity. For example, repetitive transcranial magnetic stimulation (rTMS) and 4 × 1/2 × 2 high-definition transcranial direct current stimulation (4 × 1/2 × 2 HD-tDCS) are largely center-based, with unilateral-target focus—bilateral excitation would require two rTMS/4 × 1 HD-tDCS systems. We developed a system that allows for focal, non-invasive, self-applied, and simultaneous bilateral excitatory M1 stimulation, supporting long-term home-based treatment with a well-tolerated wearable battery-powered device. Here, we overviewed the most employed M1 neuromodulation methods, from invasive techniques to non-invasive TMS and tDCS. The evaluation extended from non-invasive diffuse asymmetric bilateral (M1-supraorbital [SO] tDCS), non-invasive and invasive unilateral focal (4 × 1/2 × 2 HD-tDCS, rTMS, MCS), to non-invasive and invasive bilateral bipolar (M1-M1 tDCS, MCS), before outlining our proposal for a neuromodulatory system with unique features. Computational models were applied to compare brain current flow for current laboratory-based unilateral M11 and bilateral M12 HD-tDCS models with a functional home-based M11−2 HD-tDCS prototype. We concluded the study by discussing the promising concept of bilateral excitatory M1 stimulation for more global pain relief, which is also non-invasive, focal, and home-based.